Perhitungan Suhu Pada Bushing Transformator Unit II GI Pekalongan dengan Metode Elemen Hingga - Herawati, Afriyastuti; Rosa, Muhammad Khairul Amri; Surapati, Alex; Handayani, Yanolanda Suzantry; Anggraini, Ika Novia; Rodiah, Yuli; Nugraha, Andi (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2022)
The reliability of the power transformer depends on the performance of the its bushing. Transformer bushings subjected to hot conditions or high temperatures for a long period of time can cause bushing failure. Bushing failure can result the damage such as bursting of the conservator tank, explosion and fire. The purpose of this study was to determine the temperature hot spot on the transformer bushing at the Unit II Pekalongan Substation (GI) in order to avoid the damage of transformer. The method that used to analyze the hot spot temperature on the transformer bushing is the finite element. The finite element method is carried out by dividing the bushing parts into small elements to be calculated so that the hot spot temperature value on the transformer bushing is obtained. The result of the highest hot spot temperature on the transformer bushing which were carried out four times using the finite element method is . Based on the IEEE standard, the hot spot temperature of transformer bushing can’t be more than . This result showed that transformer bushng of Unit II Pekalongan Substation are still in the normal category.